Improved centration of the type 1 Boston Keratoprosthesis in donor carrier tissue - Yousuf M Khalifa (Dove Medical Press, 2010)
Yousuf M Khalifa1, Majid Moshirfar21Flaum Eye Institute, University of Rochester, Rochester, NY, USA; 2Moran Eye Center, University of Utah, Salt Lake City, UT, USAAbstract: The type 1 Boston Keratoprosthesis preparation requires a 3-mm central punch and an 8.5 mm or larger punch in the carrier tissue. These punches are ideally concentric, but we have found difficulty in achieving concentric punches when the larger punch is performed first. We present a modification in the preparation procedure to help minimize centration error.Keywords: Boston Keratoprosthesis, centration error